THE INVISIBLE BLACKNESS OF HARRYETTE MULLEN'S POETRY:WRITING, MISCEGENATION, AND WHAT REMAINS TO BE SEEN - Amorim, Lauro Maia (Univ Estadual Paulista-unesp, 2012)
This essay addresses the poetics of Harryette Mullen, an awarded African-American female poet whose work questions the boundaries that shape the expectations for accessible intelligibility in African-American literature. Mullen's poems skirt the edges of intelligibility by going beyond the expectations for a visible/intelligible form of language that would embrace the experience of blackness. I argue that writing in Mullen's poetry works as process of miscegenation by playing on the illegibility of blackness, beyond a visible line of distinction between what is or should be considered part of blackness itself, which engages new forms of reflection on poetry as a politically meaningful tool for rethinking the role of the black (female) poet within the black diaspora.
Keywords: Harryette Mullen; Poetry; Writing; Miscegenation; (In)visibility